Structural shocks and labour market dynamics in a small open-economy : theory and some evidence - Borda, Patrice ({Caribbean Centre for Money and Finance] [St. Augustine]TT, 2009)
Measures the persistence of labour market distortions in general and unemployment in particular, to structural shocks in the context of small open economies. Analyzes the links that might exist between shocks.